2021
DOI: 10.3390/plants10091818
|View full text |Cite
|
Sign up to set email alerts
|

Eragrostis curvula, a Model Species for Diplosporous Apomixis

Abstract: Eragrostis curvula (Schrad.) Ness is a grass with a particular apomictic embryo sac development called Eragrostis type. Apomixis is a type of asexual reproduction that produces seeds without fertilization in which the resulting progeny is genetically identical to the mother plant and with the potential to fix the hybrid vigour from more than one generation, among other advantages. The absence of meiosis and the occurrence of only two rounds of mitosis instead of three during embryo sac development make this mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 121 publications
(209 reference statements)
0
10
0
Order By: Relevance
“…The authors suggested that this was due to novel epigenetic regulation associated with the transition to polyploidy (Zappacosta et al 2014 ). Variations in methylation patterns in Eragrostis curvula were also detected after autopolyploidization by Cervigni et al ( 2008 ), Ochogavía et al ( 2011 ) and (Carballo et al 2021 ). Similarly, methylation analyses revealed that new epialleles emerged after tetraploidization of a diploid Paspalum notatum (Rodriguez et al 2012 ) and P. rufum (Siena et al 2008 ).…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…The authors suggested that this was due to novel epigenetic regulation associated with the transition to polyploidy (Zappacosta et al 2014 ). Variations in methylation patterns in Eragrostis curvula were also detected after autopolyploidization by Cervigni et al ( 2008 ), Ochogavía et al ( 2011 ) and (Carballo et al 2021 ). Similarly, methylation analyses revealed that new epialleles emerged after tetraploidization of a diploid Paspalum notatum (Rodriguez et al 2012 ) and P. rufum (Siena et al 2008 ).…”
Section: Introductionmentioning
confidence: 73%
“…Protein degradation pathway genes, codifying for F-box proteins, E3 ligases-like, the homolog of RMA3 and a TRAF-like superfamily protein, and ubiquitin-like superfamily protein like UBC28 , were found to be upregulated in apomictic nucella of Boechera (Zühl et al 2019 ). The ubiquitination pathway was differentially expressed in Eragrostis curvula (Carballo et al 2021 ) under drought stress, with five genes down- and two upregulated (Selva et al 2020 ). The Apospory locus ( HAPPY ) of Hypericum perforatum includes a homolog of ARIADNE7 , a protein involved in regulatory processes and protein degradation (Schallau et al 2010 ).…”
Section: Oxidative Stressmentioning
confidence: 99%
“…In this study, a pangenomic approach was adopted to unravel genome diversity in E. curvula species. Even though this grass is studied as an apomictic model ( Carballo et al., 2021b ), here, we focused on the alterations produced by a recent diploidization event ( Echenique et al., 1996 ) of the tetraploid cv. Tanganyika INTA to produce the Victoria genotype, obtained by in vitro culture of inflorescences ( Cardone et al., 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…All the genes assessed here are, at some point, associated with both reproduction and ploidy level. Regarding the genes that are absent in Victoria, it is important to note that after diploidization, the reproductive performance of Victoria was seriously affected ( Carballo et al., 2021b ). The lack of some genes such as RECQ4A , MEE66 , and PVA12 , which are directly involved in the reproductive pathway, could be the cause of the reduction in fertility.…”
Section: Discussionmentioning
confidence: 99%
“…2F). The mature gametophyte contains one egg cell, two synergid cells, and only one mononucleate central cell; hence, it is possible to maintain the 2:1 maternal:paternal genome contribution to the endosperm, to which cereals are very sensitive (Meier et al, 2011;Carballo et al, 2021) (Table 1).…”
Section: Cytological Characterization Of Diplosporymentioning
confidence: 99%